2007
DOI: 10.1080/01635580701308216
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Auraptene Suppresses Azoxymethane-Induced Colonic Preneoplastic Lesions in C57BL/KsJ-db/dbMice

Abstract: The current study was designed to investigate whether dietary citrus auraptene (AUR) suppresses the development of azoxymethane (AOM)-induced colorectal preneoplastic lesions in C57BL/KsJ-db/db (db/db) mice with obese and diabetic phenotypes. Female db/db and wild (+/+) mice were divided into the AOM + AUR, AOM alone, AUR alone, and the untreated groups in each phenotype. AOM was given 3 weekly intraperitoneal injections (10 mg/kg bw). AUR (250 ppm) was given in diet during the study (for 10 wk). Dietary AUR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Thereafter, the distal parts (5 cm from the anus) of the colon were cut to count the number of BCAC. To identify BCAC intramucosal lesions, the distal part of the colon (mean area, 0.7 cm 2 per colon) was embedded in paraffin, and then a total of 20 serial sections (4-Am thick each) per colon were made by an en face preparation (20,21,25). For each case, 2 serial sections were used to analyze BCAC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, the distal parts (5 cm from the anus) of the colon were cut to count the number of BCAC. To identify BCAC intramucosal lesions, the distal part of the colon (mean area, 0.7 cm 2 per colon) was embedded in paraffin, and then a total of 20 serial sections (4-Am thick each) per colon were made by an en face preparation (20,21,25). For each case, 2 serial sections were used to analyze BCAC.…”
Section: Methodsmentioning
confidence: 99%
“…The other section was used for the proliferating cell nuclear antigen (PCNA), a G 1 -to-S phase marker, immunohistochemistry to estimate the cell proliferative activity in the colonic mucosa. Immunohistochemical analyses for h-catenin and PCNA were done with the labeled streptavidin-biotin method (LSAB kit; DAKO) as previously described (20,21). Anti -h-catenin antibody (1:1,000 final dilution) was obtained from Transduction Laboratories (catalogue no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auraptene is mainly contained in citrus peel and has various remarkable biological functions as reported by many researchers (Genovese & Epifano, 2011). The physiological functions such as anti-cancer effect (Hayashi et al, 2007;Kawabata et al, 2000;Krishnan et al, 2009;Murakami et al, 1997), anti-obese effect in vitro (Genovesem et al, 2010;Kuroyanagi et al, 2008;Takahashi et al, 2008), and anti-inflammatory effect (Kohno et al, 2011;Murakami, Matsumoto, Koshimizu, & Ohigashi, 2003;Murakami et al, 2000;Tanaka, Yasui, Ishigamori-Suzuki, & Oyama, 2008) are well known. It has been suggested that detoxification and excretion of carcinogens are the most important function of auraptene for preventing carcinogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that treatment of dietary Auraptene (AUR), an antioxidant agent isolated from citrus fruit, significantly reduces the number of β-catenin accumulated crypts (BCAC) meanwhile AUR suppresses cell proliferation and increases apoptosis in C57BL/ KsJ-db/db (db/db) mice (Hayashi et al, 2007). Similar function was found in another citrus fruits extract, the citrus unshiu segment membranes (CUSMs), a waste after squeezing juice, could decrease the frequency and histological evolution of BCACs by inhibiting cellular proliferation .…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%